2021
DOI: 10.3389/fcomp.2021.642633
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Capture of Patient Behaviour for Improved Detection of Early Dementia: Clinical Feasibility and Preliminary Results

Abstract: Non-invasive automatic screening for Alzheimer’s disease has the potential to improve diagnostic accuracy while lowering healthcare costs. Previous research has shown that patterns in speech, language, gaze, and drawing can help detect early signs of cognitive decline. In this paper, we describe a highly multimodal system for unobtrusively capturing data during real clinical interviews conducted as part of cognitive assessments for Alzheimer’s disease. The system uses nine different sensor devices (smartphones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 96 publications
0
12
0
Order By: Relevance
“…More recently, multimodal representations have been explored, combining linguistic and paralinguistic aspects of communication (Haider et al, 2020;Mahajan and Baths, 2021), as well as eye-tracking and other sensor modalities (Jonell et al, 2021). Those studies combined signal processing and machine learning to detect subtle acoustic signs of neurodegeneration which may be imperceptible to human diagnosticians.…”
Section: Related Workmentioning
confidence: 99%
“…More recently, multimodal representations have been explored, combining linguistic and paralinguistic aspects of communication (Haider et al, 2020;Mahajan and Baths, 2021), as well as eye-tracking and other sensor modalities (Jonell et al, 2021). Those studies combined signal processing and machine learning to detect subtle acoustic signs of neurodegeneration which may be imperceptible to human diagnosticians.…”
Section: Related Workmentioning
confidence: 99%
“…The wearable biosensor offers many advantages, such as portability, comfort, convenience, and allowing for continuous point-of-care testing (Zhang et al, 2021a). At the same time, it Frontiers in Bioengineering and Biotechnology frontiersin.org has some drawbacks, for instance, some of them are bulky to wear, distracting, and cause tension (Jonell et al, 2021). As a result, in certain cases, some non-wearable biosensors are introduced to create an experimental environment with minimal interference to subjects and maintain the ecological validity of the recorded data, such as ambient-based in-home wireless sensors and Kinect (depth) sensors, etc.…”
Section: Body Motion Behavior Detection Of Alzheimer's Diseasementioning
confidence: 99%
“…Frontiers in Bioengineering and Biotechnology frontiersin.org clinical condition. In this way, the clinical feasibility of this sensor system is demonstrated by relating these digital biomarkers to traditional clinical assessment methods and established biomarkers (Jonell et al, 2021).…”
Section: Multimodal Detection Of Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Martinc et al ( 34 ) also used a multimodal approach to detect AD on the ADReSS dataset, using an active data representation approach ( 13 ), combining linguistic, acoustic, and temporal features and obtaining an accuracy of 93.75%. Jonell et al ( 35 ) recorded participants' language, speech, motor signs, pupil dilation, thermal emission, facial gestures, gaze, and heart rate variability of 25 patients with AD and found that multi-modality improved clinical discrimination. Recently, the transfer learning model has been widely used to diagnose AD.…”
Section: Related Workmentioning
confidence: 99%